The Simplex Lattice Design of Experiments: Formulation of Low-IFT Foam Surfactant for EOR Application - Zahari, N.F.S. (Springer Science and Business Media B.V., 2021)
The main objective of this work was to determine the optimum surfactant formulation to get low interfacial tension (IFT) and foam half-life value by using simplex lattice mixture Design of Experiment (DOE) method. A quadratic model was fitted to the first response, that is foam half-life, whereas special quartic model was fitted to IFT. Both models have been experimentally validated based on the ANOVA table. Two diagnostic tools were also used to help in investigate in diagnosing the models, which are the Normal Plot of Residuals and Box-Cox Plot. Besides that, the impacts of the surfactant component fractions on foam half-life and IFT variation were also studied followed by optimizing the models to get an optimum formulation that will produce high stability and minimum IFT value. The predicted and experimental value IFT were found to be in good agreement with value of 0.05Â mN/, which close to the predicted value of 0.04Â mN/m, whereas for foam half-life, the experimental value is 286Â s which is not in good agreement to the predicted value of 338Â s. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.